Priming Resistance to Persuasion decreases adherence to Conspiracy Theories*. (3rd July 2018) - Bonetto, Eric; Troïan, Jaïs; Varet, Florent; Lo Monaco, Grégory; Girandola, Fabien
Abstract: Research in the field of Resistance to Persuasion (RP) has demonstrated that inoculating individuals with counter arguments is effective for lowering their levels of adherence to conspiracist beliefs (CB). Yet, this strategy is limited because it requires specific arguments tailored against targeted conspiracist narratives. Therefore, we investigated whether priming Resistance to Persuasion would reduce individual adherence to CB among undergraduate student samples. A first study ( N = 81) demonstrated that participants primed by filling a RP scale had lower CB scores than control participants. This effect was directly replicated twice ( N = 205 and N = 265) and confirmed by a mini meta-analysis ( N = 519; d = .20). Practical and theoretical implications are then discussed.